Nomenclatural and taxonomic notes on three South-East Asian species of Amata (Lepidoptera: Erebidae: Arctiinae: Syntomini) - de Freina, Josef J.; Prins, Willy De (Zootaxa, 2018)
The taxonomy and nomenclature of three South-East Asian species of Amata all named leopoldi is clarified. Leopoldina leopoldi Hering, 1934 syn. n., is synonymized with Amata sperbius (Fabricius, 1787), Syntomis leopoldi Hering, 1934 is transferred to Amata as Amata leopoldi (Hering, 1934) comb. n. and Syntomis leopoldi Tams, 1935 is renamed as Amata tamsi nom. n., due to its primary homonymy with Syntomis leopoldi Hering, 1934. A synonymic list of the three species is provided, together with a colour plate of the holotypes and other relevant specimens.